Contribution of F. Martens to the Progressive Development of the International Humanitarian Law (to the 140 years of the Brussels Conference of 1874) - Ivan I. Kotlyarov (Московский журнал международного права, 2014)
The initiative of Russia to convey the Brussels Conference of 1874 of the European states to codify the laws and customs of war, where professor Martens presented his project of the Convention of the Laws and Customs of War. The participant states recognized the importance of the Russian proposal. However, due to discord between them they had not come to a common decision on agreement on the text of the International declaration of the Laws and Customs of War.